Inference to the best action and its basis in clinical expertise - Fedyk, Mark; Draughon Moret, Jessica; Sawyer, Nicolas T. (Frontiers in Psychology, 2023)
Can contemporary cognitive science explain clinical expertise? We argue that the answer could be “no”. In support of this, we provide an analysis of two of the most essential expressions of clinical expertise in nursing and medicine, the ability to run a code blue and the ability to diagnose congestive heart failure. We show how it makes sense to treat both as examples of what we call inference to the best action, and we then argue that two of the standard explanatory paradigms of cognitive science -- the Humean and Bayesian paradigms -- are unable to provide a plausible analysis of inference to the best action.